Experimental Study on the Effects of Pier Shape and Skew Angle on Pier Scour. (August 2019) - Shahhosseini, Mohammad; Yu, Guoliang
Abstract: Scouring around the bridge piers is one of the reasons for their instability, and in the absence of a suitable solution, it will eventually lead to the destruction of the structure. Therefore, studying the mechanism of scouring and effective parameters on its value is essential. In this study, using a laboratory model, this scouring phenomenon was investigated, and the effect of bridge pier shape and the skew angle between water flow and bridge pier on scouring were investigated. Experiments for four pier shapes, including a rhombus 30° inner-angle, rhombus 60° inner-angle, a cylindrical and an oblong, and three velocities include 0.191, 0.30 and 0.380 m/s, in two modes: parallel and skew-angles between stream and piers. The results show that the depth of scouring depends on the shape of the bridge pier and the angle of its placement in the flow. The best shape of the piers, the smallest scouring around it, is the rhombus 30, rhombus 60, oblong and cylindrical respectively. When the rust-shaped pier was placed in running water, in addition to less flow turbulence, the amount of scouring is also reduced. Also, due to the test with an angle between the stream and the bridge pier, the turbulence of the stream and scouring around the pier of the rhombus30 is lower than the other piers. The shape factor can be used as 1.0 for circular and oblong, and 0.9 for the shape of the rhombus 30 and the rhombus60. By analyzing the experiments, a suitable form for the bridge pier, a rhombus 30° inner-angle was proposed.